Role of synbiotics in the prevention of necrotizing enterocolitis in preterm neonates: a randomized controlled trial - B, Sreenivasa; Kumar P, Sunil; Babu MT, Suresh; K, Ragavendra (International Journal of Contemporary Pediatrics, 2017)
Background: Although survival of preterm neonates has improved in the surfactant era, necrotizing enterocolitis (NEC) continues to be a major cause of mortality and morbidity. A proposed strategy for the prevention of NEC is the administration of oral synbiotics. We evaluated the role of synbiotics in reducing the incidence and severity of NEC in preterm babies. Methods: A prospective randomized control trial was conducted in preterm neonates <34 weeks of gestation. They were randomized into two groups. The neonates in the test group were fed with synbiotic sachet with breast milk, twice daily till they reach full feeds. The neonates in the control group were fed with breast milk alone. The primary outcome was incidence and severity of NEC. Results: 200 preterm neonates were enrolled, 100 in the test group and 100 in the control group. The demographic and clinical variables were similar in both groups. The incidence of NEC was significantly lower in the test group (2 of 100 vs. 10 of 100). The incidence of stage 2 NEC was nil in the test group but 5 in control group. There were 2 cases of severe NEC (stage 3) in the control group and none in the test group. Incidence of sepsis was also significantly lower in the test group (28 of 100 vs. 42 of 100). Other secondary outcomes like age reached full feeds and duration of hospital stay were similar in both test and control groups. Conclusions: Synbiotics fed enterally with breast milk reduced both the incidence and severity of NEC.